(untitled) (Yangi O’zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2024)
The principles of social policy play a crucial role in addressing the social problems faced by women in Uzbekistan. The social policy of women is a set of principles, values, and strategies that guide the actions of governments, organizations, and individuals in addressing the social issues affecting women. In Uzbekistan, women face a range of social problems, including gender-based violence, lack of access to education and employment, and limited participation in decision-making processes. This article will discuss the principles of social policy of women in solving social problems of women in Uzbekistan.